PERKAWINAN BEDA AGAMA - Huzaini ‎ ‎ ‎ ‎ ‎ ‎ (Institut Agama Islam Negeri Metro, 2022)
Talking about interfaith marriage is no longer a new phenomenon but has become commonplace in society and even become a trend among celebrities. However, in interfaith marriages, we often encounter questions about whether or not interfaith marriages are legal and the law in Islam, whether the man or woman is Muslim. Life like this is a necessity that has become the nature or instinct of every human being. Therefore, Islam pays considerable attention to this marriage issue, including marriages between people of different religions or interfaith marriages. Religious texts prohibit Muslim marriages with polytheists. In general, apart from the laws in force in Indonesia, religious teachings also become a